Acute and chronic effects of oral administration of a medium‐chain fatty acid, capric acid, on locomotor activity and anxiety‐like and depression‐related behaviors in adult male C57BL/6J mice. Issue 1 (7th January 2022) - Shoji, Hirotaka; Kunugi, Hiroshi; Miyakawa, Tsuyoshi
Abstract: Aim: Capric acid (also known as decanoic acid or C10) is one of the fatty acids in the medium‐chain triglycerides (MCTs) commonly found in dietary fats. Although dietary treatment with MCTs is recently of great interest for the potential therapeutic effects on neuropsychiatric disorders, the effects of oral administration of C10 on behavior remain to be examined. This study investigated acute and chronic effects of oral administration of C10 on locomotor activity and anxiety‐like and depression‐related behaviors in adult male C57BL/6J mice. Methods: To explore the acute effects of C10 administration, mice were subjected to a series of behavioral tests in the following order: light/dark transition, open field, elevated plus maze, Porsolt forced swim, and tail suspension tests, 30 minutes after oral gavage of either vehicle or C10 solution (30 mmol/kg dose in Experiment 1; 0.1, 0.3, 1.0, 3.0 mmol/kg doses in Experiment 2). Next, to examine chronic effects of C10, mice repeatedly administered with either vehicle or C10 solution (0.3, 3.0 mmol/kg doses per day, for 21 days, in Experiment 3) were subjected to behavioral tests without oral administration immediately before each test. Results: The mice administrated with the high dose of C10 (30 mmol/kg) showed lower body weights, shorter distance traveled, and more anxiety‐like behavior than vehicle‐treated mice, and the results reached study‐wide statistical significance. The C10 administration at a lower dose of 0.3 mmol/kg had no significant effects on body weights and induced nominally significantly longer distance traveled than vehicle administration. Repeated administration of C10 at a dose of 3.0 mmol/kg for more than 21 days caused lower body weights and decreased depression‐related behavior, although the behavioral differences did not reach study‐wide significance. Conclusions: Although these results suggest dose‐dependent effects of oral administration of capric acid on locomotor activity and anxiety‐like and depression‐related behaviors, further study will be needed to replicate the findings and explore the underlying brain mechanisms. Abstract : Repeated oral administration of the medium‐chain fatty acid, capric acid, decreased depression‐related behavior in C57BL/6J mice. This study suggests that capric acid exerts an antidepressant effect.